Lavoro, antropologia e differenze - Ceschi, Sebastiano (Cambio. Rivista sulle Trasformazioni Sociali, 2016)
The article tackle the issues of giving analytical readability and practicable socio-cultural perspectives to the blurred and dispersed features of contemporary work. The interplay between work processes and relationships and the socio-economic, cultural, political and territorial differences of workers can be a central field to explore through empirical and ethnographic approaches, and an interesting key to access processes and dynamics characterizing post-Fordist transformations. Focusing on migration and related differences and drawing from personal research experiences, the author discusses three possible analytical domains for studying effects and counter effects of the relationship between work and difference: spaces, “cultures” of work, status. Ethnography in and of the work places, to be conducted through different levels of deepness according to real constraints, is still a fundamental tool in order to increase the presence of researchers in the workplaces and to improve socio-cultural knowledge on contemporary work.